Putting Responsible Finance to Work for Citi Microfinance - Chiu, Tzu-Kuan (2014)
This paper develops an ethical framework for responsible finance and then applies it to Citigroup (Citi), a major financial actor in the microfinance sector, to see whether it meets with such obligations. The framework consists of two categories of responsibility. The first category is the special social responsibility of financial institutions; and the second is the fundamental principles of ethical behavior in financial services. From Citigroup’s microfinance model, scope of business, and multiple roles in the market, the company seems to be fulfilling its responsibility in inclusive finance. However, judged in term of the principles of integrity, objectivity, fairness, professionalism, and diligence, it falls short of its ethical responsibility. In view of this shortcoming, Citigroup should recall its obligation to avoid conflicts of interest, to provide responsible advice, to protect clients from over-indebtedness, and most importantly, to act with integrity.
Keywords: Special social responsibility; Responsible finance; Microfinance; Ethics code; Citigroup